Teaching in times of crisis: understanding the uneven effects of the COVID-19 lockdowns on teaching practices in Zimbabwe "“ a case study of Marondera - Nhliziyo, Sarah Mazvita (Rhodes University, Faculty of Humanities, Department of Sociology)
The COVID-19 pandemic has exposed the fragility of economies in times of a global crisis while simultaneously increasing inequalities between and within countries. The pandemic responses have varied between countries with some being extremely proactive and others being quite reluctant to respond. Though it is largely a health crisis, its impact has far reaching effects that have been felt in many sectors of society including education. Billions of scholars at varying levels were forced out of school abruptly globally and unfortunately some have not been able to return to schools. The differential impact of COVID-19 in education is evident not only at a global level, but national level as well. The primary focus of this research is the impact of COVID-19 on the teaching practices applied in Zimbabwean schools. Zimbabwe, a developing nation in the southern region of Africa, has a long history of a thriving education sector recognised internationally. However, in the wake of the pandemic, the research attempts to understand the experiences of teachers in private and government schools in the hope of showing the dilapidation and unevenness of the sector, across the private-public divide. COVID-19 comes at a time when the country's economy and healthcare system continue to exhibit signs of struggle and collapse. The research made use of qualitative research methods and in-depth interviews with teachers from public and schools around the town of Marondera. The research concluded that there are wide gaps in the quality of education delivered to students in private and government schools, and that the COVID-19 lockdowns in Zimbabwe not only demonstrate these gaps but also exacerbated them.
Keywords: COVID-19 Pandemic, 2020- -- Zimbabwe; Lockdown; Social distancing (Public health) and education -- Zimbabwe; Educational equalization -- Zimbabwe; COVID-19 Pandemic, 2020- -- Economic aspects; Teaching -- Social aspects -- Zimbabwe